IN VITRO HYPOGLYCEMIC AND ANTIMICROBIAL ACTIVITY OF CUCUMIS CALLOSUS (ROTTL.) COGN. FRUIT - Panda, Siva Prasad; Kanti Haldar, Pallab; Das, Sudipta (Asian Journal of Pharmaceutical and Clinical Research, 2016)
<!–[if gte mso 9]> <![endif]–> ABSTRACT Objective: This research investigated in vitro hypoglycemic and antimicrobial activity of methanolic fruit extract of Cucumis callosus (MECC) (Rottl.) cogn. Methods: The in vitro antidiabetic ability of MECC was evaluated by inhibition studies of the digestive enzymes including Î±-amylase and Î±-glycosidase. The antimicrobial activity of extract was further evaluated against 21 laboratory strains belongs to 8 bacterial species and 4 fungal species using cupplate agar diffusion assay and agar dilution assay. Results: Our assay result suggested that the MECC exhibited dose-dependent increase in percentage inhibitory activity on Î±-glycosidase (IC 50 405.37 Âµg/ml) and Î±-amylase enzymes (IC 721.55 Âµg/ml). The results of antimicrobial activity also showed that the extract inhibited the growth of 13 strains of 7 bacterial species and all fungal species. 50 Conclusion: The observed inhibitions of Î±-amylase and Î±-glycosidase and inhibition of some microbial species suggested that the MECC may be useful in the management of diabetes mellitus and treatment of some infectious diseases. Keywords: Cucumis callosus, Diabetes, Î±-amylase, Î±-glycosidase, Antimicrobial. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE HI <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>